Fisetin Attenuates Diabetic Nephropathy-Induced Podocyte Injury by Inhibiting NLRP3 Inflammasome - Dong, Wenmin; Jia, Chenglin; Li, Ji; Zhou, Yi; Luo, Yun; Liu, Jibo; Zhao, Zhiguo; Zhang, Jiaqi; Lin, Shan; Chen, Ying (Frontiers in Pharmacology, 2022)
Diabetic nephropathy (DN) is one of the primary complications of diabetes. Fisetin is a flavonoid polyphenol that is present in several vegetables and fruits. The present study investigated the mechanisms of fisetin in DN-induced podocyte injury both in vitro and in vivo. The results revealed that fisetin ameliorated high glucose (HG)-induced podocyte injury and streptozotocin (STZ)-induced DN in mice. CDKN1B mRNA expression in the glomeruli of patients with DN decreased based on the Nephroseq dataset, and fisetin reversed CDKN1B expression at mRNA and protein levels in a dose-dependent manner in podocytes and mice kidney tissues. Furthermore, fisetin suppressed the phosphorylation of P70S6K, a downstream target of CDKN1B, activated autophagosome formation, and inhibited Nod-like receptor protein 3 (NLRP3) inflammasomes. Interfering CDKN1B reduced the protective effects of fisetin against high glucose-induced podocyte injury. Molecular docking results revealed a potential interaction between fisetin and CDKN1B. In summary, the present study revealed that fisetin alleviated high glucose-induced podocyte injury and STZ-induced DN in mice by restoring autophagy-mediated CDKN1B/P70S6K pathway and inhibiting NLRP3 inflammasome.